Comparative procedures for the sample decomposition of rocks used in organic agriculture and the determination of Cu, Fe, Mn, and Zn by FAAS - Amorim Filho, Volnei Resta; Polito, Wagner Luiz; Gomes Neto, José Anchieta [UNESP] (My University, 2004)
The aim of this work was to develop an appropriate sample preparation procedure for the flame atomic absorption spectrometry determination of Cu, Fe, Mn, and Zn in rocks used in organic agriculture as a source of macro- and micronutrients. Six different procedures were evaluated and are classified into three groups: (a) pressure digestion system with Teflon bombs, (b) conventional wet digestion in a digester heating block, and (c) closed microwave system with pressure and temperature control. Two standard reference materials and two commercial samples were analyzed. It was found that the closed microwave system required low reagent consumption, less time, and resulted in low contamination.